2015
DOI: 10.1061/(asce)mt.1943-5533.0001133
|View full text |Cite
|
Sign up to set email alerts
|

Use of Secondary Slags in Completely Recyclable Concrete

Abstract: A completely recyclable concrete (CRC) is designed to have a chemical composition equivalent to the one of general raw materials for cement production. By doing so, this CRC can be used at the end of its service life in the cement clinkering process without need for ingredient adjustments, and with improvement of the resource efficiency of cement and concrete production. Copper slag is interesting as an iron source for the production of such a CRC and can be added to concrete, either as alternative binder or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 22 publications
(41 reference statements)
1
9
0
Order By: Relevance
“…Most mixes showed almost no signs of carbonation except for some local carbonation mostly around microcracks or aggregates, which is consistent with concurrent research findings by [25]. The results of the average carbonation depths d kmean (recorded to the nearest 0.5 mm) of the tested copper slag mixes for duplicate specimens per mix are presented in Table 6.…”
Section: Carbonation Testing Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…Most mixes showed almost no signs of carbonation except for some local carbonation mostly around microcracks or aggregates, which is consistent with concurrent research findings by [25]. The results of the average carbonation depths d kmean (recorded to the nearest 0.5 mm) of the tested copper slag mixes for duplicate specimens per mix are presented in Table 6.…”
Section: Carbonation Testing Resultssupporting
confidence: 79%
“…It is possible that slumps were affected to some extent by the angular shape of the copper slag aggregate as discussed later. It is interesting that [25] also found a decrease in workability when fine aggregate was replaced by copper slag, against initial expectations. Overall however the workability results show that workable mixes can be achieved for all sand replacement levels if the w/c ratio is carefully controlled.…”
Section: Fresh Concrete Workabilitymentioning
confidence: 71%
See 2 more Smart Citations
“…The effect of some iron-rich NFM slags on the cement hydration has been investigated in the past as well. De Schepper et al [12] and Edwin et al [13] reported a retarding effect of copper slag on the hydration of cement, which was attributed to the heavy metal content of the slag, in particular Zn, which was present in considerable amounts (> 5 wt%).…”
Section: Introductionmentioning
confidence: 99%